THROUGH THE PRISM OF PREDICTIVE АNALYTICS: CULTURAL AND IDEOLOGICAL TRENDS IN THE MIDDLE EAST AND THE PROBLEM OF TERRORISM - L. L. FITUNI (Ассоциация независимых экспертов «Центр изучения кризисного общества» (in English: Association for independent experts “Center for Crisis Society Studies”), 2017)
The article is an attempt to predict the main trends of the political, cultural and ideological development of the Middle East in the  medium and long term, taking into account the impact of  international terrorism. To provide optimal solutions possible the  author identifies a number of core components. Basing this selection  he offers his vision of the likely behaviour of key state and non-state  actors as well as the forthcoming fate of the objects of their attention. In preparing the scenarios, the main methods of  predictive analytics were used: statistical analysis, intellectual  analysis of data, analysis of patterns and models conducted within  the framework of the Russian Foundation for Basic Research project  “The Phenomenon of the Islamic State” in the context of the development of a modern Eastern society. “The article is based  on an interpretation of the main conclusions and results of using those methods and methodologies. The article asserts that the recent growth of radical Islam in the East and political populism  in the West are close root causes. Despite all the differences in the  rhetoric and the outward forms, they represent a defensive response  on the part of those segments of Eastern and  Western societies that have failed to adjust to rigid paradigms of  globalization. Intra- and inter-confessional conflicts may become the  prevailing form of military threats in the region, beginning around  the 2020s. Their heralds are already visible in conflicts in Iraq, Syria, Yemen and, to a lesser extent, in Lebanon, Bahrain and on the east  coast of the Arabian Peninsula. Interstate Shiite-Sunni contradictions have so far been limited by political-ideological  confrontation and diplomatic demarches, sometimes accompanied by various embargoes, such as the recent Qatar crisis. Even the physical destruction of the selfproclaimed Islamic pseudo-state in MENA will take some time. Under favorable circumstances, ISIS units may be squeezed out of the important settlements of Syria and Iraq  within a year. This will not mean the end of ISIS. The experience of  the war with terrorist groups in Libya, Algeria, West Africa, Somalia,  Afghanistan, and Southeast Asia shows that even when driven out  into the desert or sparsely populated areas, fragmented but linked  groups of terrorists continue for quite some time to inflict harassing attacks on government forces and objects, to make long  sorties and to arrange spectacular acts of terrorism. Most likely, the  forces interested in maintaining the problems of international terrorism high on the agenda will not sit idly by but will  undertake spectacular and noteworthy actions to keep terrorism  issues in the limelight. As a result, the intensity of terrorist attacks in  the West may increase, since even limited terrorist attacks in  Europe cause more media coverage in the world media than any acts of terrorism in the Middle East. To achieve these goals, new channels and forms of imple mentation of terrorist attacks will  be used, such as terrorist acts involving children, ordinary means of  transport, during the course of mass and symbolic political events, elections, etc.